HUBUNGAN TINGKAT PENGETAHUAN PERAWAT TENTANG PEMASANGAN INFUS DENGAN KEPATUHAN MELAKSANAKAN PROTAP PEMASANGAN INFUS DI RUMAH SAKIT HATIVE PASSO - Bazrul Makatita; Silvianovelista R Losoiyo; Apriyanti Kartini Tuharea (STIKES Pasapua Ambon, 2021)
Introduction: Inserting an infusion is an invasive procedure and is an action that is often performed in hospitals. Professional nurses in providing health services are inseparable from compliance in every procedural action and are required to have the ability and skills regarding infusion according to standard operating procedures. Objective: To determine the relationship between the level of knowledge of nurses about infusions with adherence to implementing procedures for infusion at Hative Passo Hospital. Method: Cross sectional with correlational analytic approach. The population and sample are all nurses who are directly related to infusion at Hative Passo Hospital, totaling 30 people using total sampling technique. Results: Most of the nurses at Hative Passo Hospital had good knowledge about infusion as many as 27 respondents (90.0%), and had adherence to carrying out infusion procedures as many as 28 respondents (90.0%). The statistical test results obtained Fisher’s exact test value of 0.020 or p = 0.020 <α 0.5. Conclusion: There is a relationship between the level of knowledge of nurses about infusion with adherence to implementing procedures for infusion at Hative Passo Hospital. Suggestion: For nurses to always pay attention to the procedures for inserting infusions in every act of infusion to prevent complications.